In vitro model of the blood brain barrier - Mohd Nasir, Mohd Hamzah; Sharif, Mohd. Faez (Penerbit UTM Press, 2020)
Neurons and other brain cells are extremely sensitive to changes in the macro- and micro-environment especially hydrostatic pressure (intracranial pressure) and electrolyte balance. Therefore, the brain macro- and micro-environment must be strictly maintained to its physiological balance. This can only be achieved by a functional gatekeeper serving as a selective barrier between fluids circulating to and from the brain. There are two primary circulatory fluids in the brain; first is the cerebrospinal fluid (CSF) and second is the blood fluid. Nutrient and biomolecule exchange between the blood and the CSF is regulated by the blood-CSF barrier, located at the choroid plexus. The other barrier that forms a selective permeable interface in the brain environment is the blood-brain barrier (BBB), which will be the primary focus of this chapter.